Hubungan Kehamilan Tidak Diinginkan dengan Kejadian Berat Bayi Lahir Rendah di Pedesaan Pulau Jawa (Analisis Data SDKI 2017) - Asri Mutiara Putri; Sudarto Ronoatmodjo (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2022)
Background: There was an increase in the proportion of birth weight less than 2500 grams from 5.7 in 2013 to 6.2 in 2018. Several provinces in Java Island also still have the proportion of LBW above the average proportion of LBW in Indonesia (> 6.2 %) such as Banten, West Java, Yogyakarta Special Region, and East Java. Maternal characteristics such as rural residence and unwanted pregnancy status are related to low birth weight. This study aims to determine the relationship between unwanted pregnancy and LBW events in rural areas in Java Island.Methods: This study was conducted by analysing secondary data from the results of the 2017 Indonesian Demographic and Health Survey (IDHS). The sample in this study consists of all live births in the last 5 years prior to the survey with reports of birth weight less than 2500 grams born to women aged 15- 49 years in rural Java Island when the survey took place and was successfully interviewed, and has a complete answer (no answer missing).Result: After weighting, 1821 samples were obtained. The result found that the proportion of LBW events in rural areas in Java Island is 6.3%. Meanwhile, of all pregnancies during the study period, 13.5% were unwanted pregnancies. The results of the multivariate analysis showed that there was no significant relationship between unwanted pregnancy status and LBW in rural areas in Java Island after adjusted by maternal age, mother's education level, maternal employment status, economic level, problems in getting health care/treatment, ANC, and parity (POR = 1.31, 95% CI = 0.72-2.38).Conclusion: It is necessary to measure variables more accurately in the questionnaire and carry out further research by including other risk factors.